The potential of Lai fruit seeds (Durio kutejensis) as a prebiotic source for poultry - Fajrih, Nurul; Anindyasari, Dinar; Ichsan Haris, Much; Faisal Fanani, Anhar; Indana, Khoiru; Rizkuna, Akhmat (Politeknik Negeri Jember, 2025)
Lai (Durio kutejensis) is an endemic fruit of Kalimantan whose seeds have potential as a prebiotic source. This study aimed to identify the types of prebiotics in Lai fruit seeds and evaluate their potential for the growth of lactic acid bacteria. The study was conducted using a Completely randomized design (CRD) with four treatments and six replications. The parameters observed included proximate composition, resistant starch content, and total bacteria. Proximate analysis was carried out with three treatments: Lai seed flour (LSF), boiled Lai seeds (BLS), and roasted Lai seeds (RLS). In vitro tests used cultures of Lactobacillus plantarum and Lactobacillus casei treated with LSF at three levels (T1: 1%, T2: 2%, T3: 3%, and T0: without LSF). In conclusion, LSF has strong potential as a novel prebiotic source due to its resistant starch content and its ability to promote lactic acid bacterial growth. These preliminary results may serve as a basis for developing alternatives to antibiotic growth promoters (AGP) in poultry.